1983
DOI: 10.1172/jci110816
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in uremia. Characterization of insulin action, binding, and processing in isolated hepatocytes from chronic uremic rats.

Abstract: A B S T R A C T We have developed a model in the rat that leads to a predictable degree of severe uremia to study the role of the liver in the insulin-resistant state of uremia. The uremic animals were euglycemic and had increased serum immunoreactive insulin when compared with their pair-fed controls. Insulin action, binding, internalization, and degradation were characterized in freshly isolated hepatocytes from uremic animals, sham-operated pair-fed, and ad lib.-fed controls.The basal rate of aminoisobutyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…The uremic animals have elevated serum triglyceride and normal serum cholesterol when compared with their pair-fed, age-, and weight-matched controls. Also, these uremic rats are hyperinsulinemic and normoglycemic (8). These characteristics of experimental uremic rats are similar to those found in uremic humans (30,31), thus making it a suitable animal model to investigate these problems.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The uremic animals have elevated serum triglyceride and normal serum cholesterol when compared with their pair-fed, age-, and weight-matched controls. Also, these uremic rats are hyperinsulinemic and normoglycemic (8). These characteristics of experimental uremic rats are similar to those found in uremic humans (30,31), thus making it a suitable animal model to investigate these problems.…”
Section: Discussionsupporting
confidence: 61%
“…We have recently demonstrated that the liver in uremia is insulin resistant with regard to amino acid transport, which is not due to defects either in insulin binding or its internalization (8). DeFronzo et al (7) have demonstrated a normal suppression of hepatic glucose production by insulin in uremic patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations